MODEL PREDIKSI FINANCIAL DISTRESS : PENGARUHNYA TERHADAP KINERJA SAHAM INDUSTRI TEKSTIL DAN GARMEN DI INDONESIA - Riantani, Suskim; Delvia, Sherly; Sodik, Gugun (BISMA: Jurnal Bisnis dan Manajemen, 2020)
This study aims to predict the possibility of Financial distress in the textile and garment industry using the Altman Z-score prediction model and analyze the impact of Financial distress on the company's stock performance as measured by stock returns. This research used descriptive analysis and verification methods. Applying a purposive sampling method, the research sample consisted of 15 issuers from the textile and garment industry during the observation period of 2012-2016. This research used panel data regression to analyze research data. The results showed that one company did not experience financial problems, one company had potential financial problems, and the 13 other companies experienced Financial distress. The results of model testing showed that Altman Z-score can be used to predict Financial distress conditions in the textile and garment industry for the 2012-2016 period. The results of hypothesis testing showed that only one ratio of the Altman Z-score model has a significant effect on stock returns, i.e., market value of equity to book value of debt, while other ratios of working capital to total assets, retained earnings to total assets, earnings before interest and taxes to total assets, and sales to total assets have no significant effect on stock returns. These findings imply that the investors in the textile and garment industry attentively observe the company's market value in making any investment decisions. Keywords: Altman Z-score, Financial distress, stock returns, textile and garment industry